Printed Telugu Numeral Recognition based on Structural, Skeleton and Water Reservoir Features - Satyanarayana, Y V V; Babu, U.Ravi; Permal, S Maruthu (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Selection of feature extraction method is most important factor in achieving high recognition performance in automatic numeral recognition systems In this paper, a new proposed system for Telugu printed numeral characters recognition using number of contours, skeleton feature, water reservoir features, and ratio of length of Top line to bottom line of the image. Printed Telugu numerals are scan converted to binary images and extract the features irrespective of size of the image. The proposed method is applied with success to a database of 3150 printed multi-font printed Telugu numerals The recognition accuracy is achieved 100%. The experimental results obtained are encouraging and comparable with other methods found in literature survey. The novelty of the proposed method is free from size normalization and without classification method.